Contact, typology and the speaker: the essentials of language - Ansaldo, Umberto (ELSEVIER SCI LTD, 2004)
This paper focuses on some of the theoretical assumptions presented in Enfield, 2003 (Review of ‘Enfield, N.J., 2003. Linguistic Epidemiology: Semantics and grammar of language contact in mainland Southeast Asia. Routledge Curzon, London and New York, pp. xv + 397’) and their consequences for contemporary linguistic theory. In particular, I revisit three fundamental dimensions underlying language contact: multilingual practices of speech communities, modes of transmission and typological diversity. These three dimensions, I argue, are not only the reasons for contact to occur but the fundamental driving forces behind language change (and variation) at large. In this view, the dichotomy typically presented as ‘contact-induced’ or ‘external’ vs. ‘normal’ or ‘internal’ change needs to be significantly revised, if not dissolved, since a non-idealized view of language change as the one advocated by Enfield presents us with a reality in which the role of contact can hardly ever be overlooked.